Encouragement Germination of Potato Seed Cultivars (Solanum tuberosum L.) - A.A. Kandil; Sharief, A.E.; Abd El-Atif, A.M.Y. (Journal of Basic & Applied Sciences, 2012)
A greenhouse experiment were conducted to study encouragement germination capacity of some potato tuber cultivars. The mean aim of this experiment was to assess the effect of some plant growth regulators treatments i.e. IAA and GA3, soaking time i.e. at (10 minutes, 20 minutes and 30 minutes on some germination and vegetative parameters of some potato cultivars i.e. Cara, Draga and Spunta. The results showed that Cara cultivar recorded highest germination index followed by Cv. Spunta without significant differences between them. Draga cultivar recorded tallest plant, highest fresh weight and dry weight in gm/plant followed by Cv. Cara for plant height only and followed by Cv. Spunta for fresh and dry weight without significant differences between them. Highest germination index percentage, tallest plants and highest fresh and plant dry weight were obtained from soaking tubers in GA3 at 10 ppm plus IAA at 6 ppm. While, soaking tubers in GA3 at concentration of 10 ppm produced highest mean of germination time. Results clearly indicated that soaking tubers for 30 minutes produced highest fresh weight followed by soaking for 20 minutes without significant differences between them. The interaction among cultivars and growth regulator treatments recorded significant differences on mean germination time, fresh weight and dry weight. Within this context, it is important to recognize the role of some growth regulators, soaking times and their interactions on encouragement germination capacity of some potato tuber cultivars.